Sufficient Cav-1 levels in the endothelium are critical for the maintenance of the neurovascular unit in the retina - Wang, Yixin; Halawa, Mahmoud; Chatterjee, Anupriya; Eshwaran, Rachana; Qiu, Yi; Wibowo, Yohanes Cakrapradipta; Pan, Jianyuan; Wieland, Thomas; Feng, Yuxi (Molecular medicine, 2023)
Caveolin-1 (Cav-1) is a pivotal protein in the plasma membrane. Studies on homozygous Cav-1 deficient mice revealed that Cav-1 is essential for endothelial function and angiogenesis in the retina. However, whether a reduction in Cav-1 content hampers the neurovascular unit (NVU) in the retina is unclear. Thus, this study examines the NVU in the retinas of heterozygous Cav-1 deficient (Cav-1+/−) mice and analyzes possible underlying mechanisms. The vascular, glial and neuronal components in the retina were evaluated using retinal morphometry, whole mount retinal immunofluorescence staining, histological analysis and optical coherence tomography. In addition, immunoblotting and immunofluorescence staining, subcellular fractionation, biotin labeling of cell surface proteins, and proximity ligation assay were employed to detect expression and localization of proteins in the retina or endothelial cells (ECs) upon knockdown of Cav-1 with Cav-1 siRNA. Cav-1+/− retinas showed a significant reduction in pericyte coverage along with an increase in acellular capillaries compared to controls at 8 months of age, but not at 1 month. A significant loss and obvious morphological abnormalities of smooth muscle cells were observed in 8-month-old Cav-1+/− retinal arterioles. Macroglial and microglial cells were activated in the Cav-1+/− retinas. A transient significant delay in retinal angiogenesis was detected in Cav-1+/− retinas at p5, which was however no longer detectable at p10. The Cav-1+/− retinas displayed increased vascular permeability and a notable reduction in VEGFR2 content at 8 months. In vitro, siRNA-mediated knockdown experiments in ECs revealed that the loss of Cav-1 in ECs resulted in decreased levels of VEGFR2, VE-Cadherin and their interaction at the plasma membrane as well. Our results indicate that a sufficient Cav-1 level over 50% of its normal abundance is vital for the proper localization of VEGFR2 and VE-cadherin, likely in a complex, at the plasma membrane, which is essential for the maintenance of normal NVU in the retina.